(untitled) (Proceedings of the World Conference on Media and Mass Communication, 2023)
Learning how to effectively communicate in our media-centered digital world is crucial for all professionals. However, it holds even greater importance for health professionals, given their primary objective of improving people’s health. Therefore, it is imperative to dedicate significant effort to designing Computer Science (CS) courses that cater to the specific needs of these professionals, equipping them with the skills and capabilities of modern digital communication. Developing CS courses specifically tailored for non-CS majors is particularly significant, as it reduces the likelihood of failure. In this study, I aim to outline the process of identifying relevant directions and tools, and designing a comprehensive course plan that enables professionals to acquire the necessary CS skills. By pinpointing topics that are directly applicable to their future professions, the course will teach professionals how to effectively utilize and design digital systems. To conduct this research, the doctoral degree course "Informatics for the Psychology of Health" at the University of Cagliari has been selected as a case study. Using qualitative methods, I assessed the satisfaction levels and perceived usefulness of the course among students. Through this investigation, numerous valuable directions were identified, along with a concise collection of free and open-source tools that will provide students with the knowledge they require to independently create and design digital interactive media. By adopting this approach, courses tailored to professionals can be designed, effectively reducing high dropout and failure rates.